The Effect of Product Quality and Location on Consumer Satisfaction Through Repeat Repurchase Intention - Nur Wulan Lovitasari; Nina Nurhasanah (PT Inovasi Pratama Internasional, 2025)
The competition in the F&B business, especially fast food, is getting tighter along with the busy lifestyle of society. Many people choose fast food because it is practical and efficient, especially after work or school. This study aims to analyze the effect of product quality and location on consumer satisfaction, through repurchase intention in one of the F&B companies in Tangerang City. The method used is quantitative with a positivistic approach, using research instruments to collect data from certain samples, then analyzed statistically to test the hypothesis. The independent variables in this study are product quality and location, the intervening variable is repurchase interest, and the dependent variable is consumer satisfaction. The results showed that product quality and location have a significant direct effect on repurchase intention. Repurchase intention also has a direct positive effect on consumer satisfaction. In addition, there is an indirect effect of quality and location on satisfaction through repurchase interest. The factors in this model explain 72.8% of the variation in consumer satisfaction, approaching a maximum of 100%.